1997
DOI: 10.1136/bmj.315.7103.275
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pregnancy in insulin dependent diabetic women: results of a five year population cohort study

Abstract: Objective: To monitor pregnancies in women with pre-existent insulin dependent diabetes for pregnancy loss, congenital malformations, and fetal growth in a geographically defined area of north west England. Design: Population cohort study. Setting: 10 maternity units in Cheshire, Lancashire, and Merseyside which had no regional guidelines for the management of pregnancy in diabetic women. Subjects: 462 pregnancies in 355 women with insulin dependent diabetes from the 10 centres over five years (1990-4 inclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
320
5
10

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(373 citation statements)
references
References 13 publications
38
320
5
10
Order By: Relevance
“…Future studies should make use of placental cell lines that might express adiponectin and adiponectin receptors endogenously to dissect further their signalling properties, including the dichotomy between the secretion and expression of adiponectin with IL-6 and leptin. With regard to GDM placentae compared with controls, future studies are needed to investigate not only the secretion of placental adiponectin and its regulation by cytokines in an explant system, but also any differences in p38 and ERK1/2MAPK that may exist, given the higher miscarriage rates in diabetic pregnancies [35,36]. Moreover, it will be interesting to investigate further what effect these cytokines have on adiponectin and its receptors in placentae, not only in GDM but also in those with type-1 diabetes mellitus, whose offspring are known to be at increased risk of developing obesity, impaired glucose tolerance and type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should make use of placental cell lines that might express adiponectin and adiponectin receptors endogenously to dissect further their signalling properties, including the dichotomy between the secretion and expression of adiponectin with IL-6 and leptin. With regard to GDM placentae compared with controls, future studies are needed to investigate not only the secretion of placental adiponectin and its regulation by cytokines in an explant system, but also any differences in p38 and ERK1/2MAPK that may exist, given the higher miscarriage rates in diabetic pregnancies [35,36]. Moreover, it will be interesting to investigate further what effect these cytokines have on adiponectin and its receptors in placentae, not only in GDM but also in those with type-1 diabetes mellitus, whose offspring are known to be at increased risk of developing obesity, impaired glucose tolerance and type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of congenital malformation in type 1 diabetic pregnancy is estimated to be 4.2% to 9.4% compared with approximately 1% in the general population [1][2][3]. Although a planned pregnancy with optimal blood glucose control and folic acid supplements at the time of conception reduces the risk of congenital malformations, a recent prospective study showed that the incidence of congenital malformations is still elevated in women with type 1 diabetes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a growing number of pregnant women have type 1 diabetes and are predisposed to perinatal complications associated with maternal hyperglycaemia, including congenital malformations, macrosomia and fetal asphyxia [3]. Numerous studies indicate that the rates of perinatal complications among type 1 diabetic patients are still substantially higher than those of the general population [4][5][6][7][8][9][10][11]. Only a few centres have shown improvement in the outcomes of type 1 diabetic pregnancies in recent decades [12,13].…”
Section: Introductionmentioning
confidence: 99%